Upcycle Jaket Denim Sebagai Media Eksplorasi Teknik Slashing Kombinasi Limbah Perca Sumber Ide Fireworks - Ayu Artamevia Katerina Putri; Yuhri Inang Prihatina (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The slashing technique is a technique of manipulating the fabric by sewing several piles of fabric and then cutting according to the bias while still showing the bottom layer.  This study aims to find out the process of exploring the design and finished results of the denim jacket upcycle as a medium for exploring slashing techniques in combination with patchwork waste and fireworks ideas. The research method using the double diamond method includes 4 stages: Discover collects information about the final effect of fireworks and designs slashing motif exploration, Define creates a moodboard "De'Slash Fireworks" to create a slashing exploration table on denim jacket design, Develop into 9 designs and makes initial trial/prototype experiments, Deliver design selection and realize the manufacture of 3 denim jacket upcycle products,  Then a feasibility test was carried out. The data collection instrument for this study uses observation sheets to textile experts on the details of fabric slashing. The data analysis technique uses quantitative descriptive analysis techniques by determining the mean or average. The results show that based on the total results of the overall aspect, it was obtained that design 1 is more in demand by observers. The inspiration for the final effect of the fireworks can be visualized into the exploration of slashing techniques with the right contrast with the colors of red, yellow, blue patchwork fabric.